2016
DOI: 10.1021/acsami.6b02156
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Ternary Artificial Nacre Nanocomposites Based on Reduced Graphene Oxide and Nanofibrillar Cellulose

Abstract: Inspired by the nacre, we demonstrated the integrated ternary artificial nacre nanocomposites through synergistic toughening of graphene oxide (GO) and nanofibrillar cellulose (NFC). In addition, the covalent bonding was introduced between adjacent GO nanosheets. The synergistic toughening effects from building blocks of one-dimensional NFC and two-dimensional GO, interface interactions of hydrogen and covalent bonding together result in the integrated mechanical properties including high tensile strength, tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 31 publications
1
81
0
Order By: Relevance
“…Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the 1D and 2D building blocks can lead to sliding effects, crack deflection and crack bridging, thereby enhancing the strength and toughness of such composite materials in a synergistic manner2122. Recently, several studies have addressed the design and mechanical characterization of ternary artificial nacre232425262728. For instance, Wang et al 24.…”
mentioning
confidence: 99%
“…However, owing their comparably soft matrix material, they exhibit only a low Young’s modulus25262728. In order to achieve a ternary system that combines good tensile strength with high stiffness and form stability, designing a ceramic-based ternary system represents a promising approach.…”
mentioning
confidence: 99%
“…Other 1D building blocks, such as cellulose nanocrystals (CNCs) [90] and nanofibrillar celluloses, [91,92] can also be introduced to construct a synergistic effect in bioinspired nanocomposites. Recently, Xiong et al [90] reported an ultra-stiff ternary bioinspired nanocomposite by assembling GO nanosheets and polyethyleneimine (PEI)-modified CNCs.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%